A Next Generation Test Framework for Automated Storage System Readiness Validation - Hagerott, S.G.; Balasubramanian, S. (2006 IEEE Autotestcon, 2006)
A next generation test framework is presented which offers automated electrical and mechanical manipulation of storage system components. This automated manipulation of storage system components in a controlled test environment enables long- term application of maintenance and fault profiles to validate high availability of the storage system to the network. This test framework can be readily extended at low cost to other electromechanical components to validate their system readiness. The salient attributes of the framework's architecture, deployed components, and application programming interface (API) are presented. A concluding case study is provided to illustrate the successful application of this test automation framework to enterprise class RAID storage system testing.